An Analysis of The Students’ Difficulties in using preposition - Ilham Ilham (Universitas Syiah Kuala, 2018)
Preposition is considered as one of the most difficult part of speeches for students to learn. Some studies also showed that students often encountered significant problems in answering question about prepositions in english grammar test. Therefore, this research had the purpose to analyze difficulties faced by the students in using preposition. In order to find out the aim,the preposition test was used as an instrument in this research. It was used all junior high school students class VIII at MTsN Rukoh, Banda Aceh as the population, whereas the students class VIII 1, which were taken randomly, were selected as the sample in this research. The preposition test contained 20 multiple choice question and 10 essay Question. The result of the test showed that the most difficult type of prepositions was preposition of manner,then it was followed by preposition of time ( the second most difficult for the students), and preposition of place ( the least difficultfor the students). Thus, it is suggested that teachers give more practices related to problems with prepositions of manner as the hardest preposition for students to learn while teaching English grammar in classroom.